Dependentyzm w socjologii polskiej. Tezy do dyskusji = Dependentism in Polish sociology. Ideas for discussion - Korab, Kazimierz (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article is aimed at opening the discussion on factors and mechanisms hindering theoretical creativity of Polish sociologists. It introduces the notion of "dependentism" as an essential instrument of the analysis of this phenomenon, which in Poland (and in many other countries) has a relatively long history. It defends the role of reception as a very important developmental factor. It also presents dependentism in the context of modernization as well as the westernization process, describing negatives consequences ("junk science") and suggesting some solutions.
Keywords: dependentyzm; socjologia polska; dependentism; polish sociology